Enhancing Pre-K Teachers’ Personal and Professional Transformation by Articulating Two University Extension Approaches: A Reflection - Maturana Patarroyo, Liliana Maria; Uribe Hoyos, Claudia María (Íkala, Revista de Lenguaje y Cultura, 2018)
University extension has been expected to fill the existing gap between academia and society in order to improve universities and contribute to societal development. Different types of interventions have been sought, professional development programmes being an example. However, professional development programmes intended for pre-K teachers have been significantly scarce in the field of in-service teacher education in Medellín, Antioquia. This paper reflects on a pedagogical experience through a professional development programme resulting from a joint effort between Universidad Católica Luis Amigó, a local private company, and a local government office. The Pre-K English Teacher Professional Development Programme (in Spanish, Programa de Desarrollo Profesional Docente: Pre-K English) is aimed at (re)defining teaching strategies and developing the communicative dimension of English in a group of about 425 pre-K teachers and librarians from different local public schools across the city and in its surrounding rural areas. Such didactic transformation and language development contributed to the English language being introduced gradually and naturally in the pre-K setting; however, the programme’s inner dynamic and pedagogical interests proved not to be in alignment with the interests and expectations of the University extension division, enterprise, or local government office.